Evaluation of the concentration of suspended particles in underground subway stations in Tehran and its comparison with ambient concentrations - Sareh Daneshgar; Rahim Zahedi; Omid Noudeh Farahani (Annals of Environmental Science and Toxicology - Peertechz Publications, 2022)
Subway lines are responsible for 20% of the total passenger traffic in Tehran. Particulate matter is one of the most important major pollutants in subway stations and increasing their concentration leads to numerous health consequences for passengers and subway employees. This study aims to investigate the concentration of PM10 and PM2.5 in four underground metro stations and compare them with the concentration of these particles in the open air. Seasonal sampling (April 2018 - April 2019) of particulate matters was conducted in the middle months of all four seasons for one week in the middle months of each season at peak traffic times from 8am to 12am, at three locations (entrance, middle, and exit in each station) and also at outside ambient of each station. The results are then compared with the relevant standards. The main sources of suspended particulate matter in the underground subway stations were due to passenger traffic, train piston pressure, floor cleaning, maintenance operations, wheel-rail wear and braking, and the performance of the ventilation system in the subway station. The results of the monitoring measurements in this study showed that the annual average concentrations of PM10 and PM2.5 in the four underground subway stations were 68 μg/m3 and 47 μg/m3 and in the outdoor ambient around these stations were 42 and 29 μg/m3, respectively. Also, this study showed that in the four underground subway stations, the annual average concentrations of PM10 and PM2.5 were 1.5-1.7 times higher than those in the outdoor ambient, respectively.